Digitalisasi Sistem Monitoring pH Air Pada Instalasi Pengelolaan Air Limbah Laboratorium BSPJI Palembang Satker Kementerian Perindustrian Berbasis Android - Fajryn, Fikry; Setiawan, Herri; Sartika, Dewi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
The wastewater management system is an important part of maintaining the cleanliness and quality of the environment. One of the parameters that need to be monitored regularly is the level of acidity or pH of the wastewater. This study aims to develop an Android-based wastewater pH monitoring system as a user interface and digitization process using Arduino and IoT modules as the leading processors. This application is also equipped with a real-time database that can be monitored at any time, pull report recaps using the Cloud Google Spreadsheet, and use the WhatsApp BOT as a chat notification that can notify the user if there is a drastic change in the pH value of wastewater from a predetermined standard value. This system consists of several pieces of hardware, namely a pH sensor, temperature sensor, Arduino module, IoT module, LCD, and a user interface using Android, which is simple and easy to read. In its implementation, this system can provide several benefits for wastewater management officers so that they can always monitor the pH level of wastewater in real-time through their Android devices without the need to be physically present to take and measure samples at the management location. This condition can improve efficiency in monitoring and facilitate taking actions and decisions if there is a significant change in the pH of the wastewater. In conclusion, using an Android-based wastewater pH monitoring system is very effective and efficient, especially for officers and analysts, and this Android-based wastewater pH monitoring system also has the accuracy of the measurement results. The accuracy of these measurement results is obtained from the results of a comparison of water pH measurement tests made with a pH meter at the Palembang BSPJI Laboratory, which has been accredited by the National Accreditation Committee (KAN) and has an Average Square Error of 0.02 where this value according to Standard IEC No.13b-23 is still within good tolerance limit is not more than 0.05. This states that the created water pH monitoring system produces valid and accurate data